2013
DOI: 10.1111/1471-0528.12394
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity changes significantly throughout all trimesters of pregnancy compared with the nonpregnant state: a prospective study

Abstract: Objective Platelets play an important role in the pathophysiology of uteroplacental disease and platelet reactivity may be an important marker of uteroplacental disease activity. However, platelet reactivity has not been evaluated comprehensively in normal pregnancy. We sought to evaluate platelet reactivity using a number of agonists at defined time points in pregnancy using a novel platelet assay and compare these with a nonpregnant cohort.Design Prospective longitudinal study.Setting Outpatient department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…Based on these reports [20][21][22], the significant positive correlation between MPV and number of PA observed in this study implied that PA count in our system may have reflected platelet reactivity. Therefore, the consistently lower PA count in addition to lower degree of fall in platelet count in the blood of pregnant women than in non-pregnant women in this study strongly suggested that platelet reactivity is reduced in early pregnancy, consistent with results of the previous study by Burke et al [19].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on these reports [20][21][22], the significant positive correlation between MPV and number of PA observed in this study implied that PA count in our system may have reflected platelet reactivity. Therefore, the consistently lower PA count in addition to lower degree of fall in platelet count in the blood of pregnant women than in non-pregnant women in this study strongly suggested that platelet reactivity is reduced in early pregnancy, consistent with results of the previous study by Burke et al [19].…”
Section: Discussionsupporting
confidence: 92%
“…These reports led to the misunderstanding that platelet reactivity in early pregnancy is similar to that in non-pregnant women, but increases gradually with advancing gestation, especially in women complicated with HDP. Therefore, the results of the study of Burke et al [19] indicating reduced platelet reactivity in early pregnancy was surprising. Burke et al [19] reported that collagen-induced platelet aggregation was lowest during the first trimester, increased in the second and third trimesters and became comparable to that in non-pregnant women.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The increase in PA counts in CWB was lowest during the 1 st trimester and greatest approximately 1 month postpartum in both singleton and twin pregnancies, consistent with the results of recent studies [18,28]. Collagen-induced platelet aggregation is significantly reduced in the 1 st trimester of pregnancy compared to non-pregnant women [28].…”
Section: Discussionsupporting
confidence: 90%